Impact of a standardized perioperative care protocol on functional and radiographic outcomes following transforaminal lumbar interbody fusion for degenerative spondylolisthesis: a 2-year randomized controlled trial - Zhao, Yixin; Wu, Jiangnan; Zhang, Zhenzhen; Wang, Yuqian; Li, Baoli (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the efficacy of a comprehensive, standardized perioperative care protocol (SPCP) vs. conventional care on functional recovery, radiographic outcomes, and quality of life in patients undergoing transforaminal lumbar interbody fusion (TLIF) for low-grade degenerative lumbar spondylolisthesis.MethodsThis was a single-center, prospective, randomized controlled trial conducted between January 2018 and June 2023. A total of 382 patients were randomized to either the SPCP group (n = 191) or the conventional care (control) group (n = 191). The SPCP incorporated preoperative education, nutritional optimization, standardized anesthesia and surgical techniques, and a structured, goal-directed postoperative rehabilitation program. The control group received routine institutional care. The primary outcome was the change in the Oswestry Disability Index (ODI) score at 2-year follow-up. Secondary outcomes included Japanese Orthopaedic Association (JOA) scores, Visual Analog Scale (VAS) for back and leg pain, Short Form-36 (SF-36) quality of life scores, radiographic outcomes (fusion rate, segmental lordosis, disc height), length of hospital stay (LOS), and postoperative complications. Assessments were performed at baseline, 3 months, 6 months, 1 year, and 2 years.ResultsAt the 2-year follow-up, the SPCP group demonstrated a significantly greater improvement in ODI scores compared to the control group (mean change: −30.0 vs. −25.5 points; mean difference: −4.5, 95% CI: −5.9 to −3.1; P < 0.001). The SPCP group also showed superior JOA scores (27.5 vs. 23.1; P < 0.001), lower VAS back pain scores (1.1 vs. 2.4; P < 0.001), and higher SF-36 Physical Component Summary (PCS) scores (48.2 vs. 42.5; P < 0.001). Radiographically, the SPCP group achieved a higher fusion rate at 2 years (94.4% vs. 88.7%; P = 0.018) and better maintenance of segmental lordosis. Mean LOS was significantly shorter in the SPCP group (7.5 ± 2.1 vs. 9.8 ± 2.5 days; P < 0.001), with a lower overall 90-day complication rate (8.4% vs. 19.4%; P = 0.002).ConclusionImplementation of a comprehensive SPCP significantly enhances long-term functional recovery, improves radiographic fusion rates, elevates quality of life, and reduces complications and hospital stay for patients undergoing TLIF for degenerative spondylolisthesis. This protocol-driven approach represents a valuable strategy for optimizing patient outcomes and healthcare efficiency in spine surgery.Clinical trial registrationClinicalTrials.gov, identifier NCT07104448.